Implementasi Karakter Disiplin dalam Kurikulum 2013 Pada Bidang Studi PAI di SMA Islam Terpadu Darul Hikmah - Yusuf, Muhammad; Ritonga, Mahyudin; Mursal, Mursal (Jurnal Tarbiyatuna, 2020)
This research aims to describe the form of character discipline implementation in the 2013 curriculum of PAI field of study, the implementation aspects that will be described include: 1) planning of Character education discipline on curriculum 2013 of PAI field of study, 2) implementation of Character education discipline in curriculum 2013 field of study and 3) discipline character Education evaluation in PIE Curriculum 2013. For the smoothness of the study designed using qualitative descriptive approach, data sources include principals, curriculum representatives, student representatives, religious teachers and some of the students selected in snowball sampling, the technique of data analysis used is classification, reduction, and withdrawal of conclusions, to ensure the validity of data is used triangulation. From the results of the research known that: 1) the planning of character education is drawing from the Learning Plan and learning tools and methods used by teachers. 2) The implementation of disciplinary character is carried out through the Uswah Hasanah, routine activities at school, extracurricular and cooperation between the parents and the school. 3) The evaluation of the discipline of character education is carried out continuously through teacher observation, peer assessment and self-assessment.